Is Cu3SbSe3 a promising thermoelectric material?1. Issue 53 (11th June 2015) - Wei, Tian-Ran; Wu, Chao-Feng; Sun, Wei; Pan, Yu; Li, Jing-Feng
<x xml:space="preserve">Abstract</x> Cu3SbSe3 characterized by ultralow thermal conductivity is a wide-gap, nondegenerate semiconductor with a large effective mass and deformation potential, yielding zTmax = 0.25.